Diversity of macromoths (lepidoptera : heterocera) in mount Serambu, Bau, Sarawak - Izyan Afiqah, binti Saiful Alyazan. (Universiti Malaysia Sarawak, UNIMAS, 2013)
A study of species diversity and abundance of moths was conducted in Mount Serambu, Bau, Sarawak for 20 days. A total of 407 species identified from 967 individuals comprised of 16 families were captured using Modified Pennsylvanian light traps during this study. The family Geometridae (27.03%), Noctuidae (19.41%) and Arctiidae (15.23%) were found to be abundant at Mount Serambu. There were 234 singleton individuals found for this study. Many species of the moth collected are common. The Shannon Diversity Index for lower elevation and upper elevation are H’=5.166 and H’=5.035 respectively. The overall total species richness and abundance were found at the lower elevation. In this study, there are several endemic species in Borneo that that had been caught that are Orvasca rufalba (Lymantriidae: Lymantrinae), Euproctis viridoculata (Lymantriidae: Lymantrinae) and Hyposidra altivolescens (Geometridae: Ennominae).